Results of Cleaning Oil Smoke Gases from Atmospheric Air - Hurmamatov A. M.; Boyto’rayev S. B. (Research Parks Publishing LLC, 2023)
The article considers the parameters that change as a result of the volume consumption of the proposed new device. As a result of changing the volume flow, the volume of the absorbent, the volume of absorbed gas, and the change in the mass of inert gas in the purified gas were analyzed. In this case, the effects of mutual forces between the phases in the absorption device were analyzed. An absorption process was used to effectively purify oils.